2001
DOI: 10.1021/ma0110958
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Porosity Characterization of Highly Cross-Linked Polymer Resins Derived from Multifunctional (Meth)acrylate Monomers

Abstract: Permanently porous polymer resins derived from multifunctional (meth)acrylate monomers have been prepared by suspension polymerization. The dry state porosity characteristics have been evaluated using N2 sorption and Hg intrusion porosimetry, and the results correlated in terms of the three-dimensional cohesion parameter, δ t , of the polymers and porogens. The pore size distributions of almost all resins cover a broad range from micro- through meso- to macropores. The porosity data had to be computed from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Similar findings were presented before for permanently porous polymer resins derived from multifunctional (meth)acrylate monomers [2,14]. Flodin and co-workers have noted that the size of smaller pores of diameter about 4 nm (determined from N 2 sorption data) is independent both of TRIM and initiator concentrations, while the size of large pores (probed via Hg intrusion) is clearly dependent on monomer concentration.…”
Section: Analysis Of Texture and Morphologysupporting
confidence: 82%
See 1 more Smart Citation
“…Similar findings were presented before for permanently porous polymer resins derived from multifunctional (meth)acrylate monomers [2,14]. Flodin and co-workers have noted that the size of smaller pores of diameter about 4 nm (determined from N 2 sorption data) is independent both of TRIM and initiator concentrations, while the size of large pores (probed via Hg intrusion) is clearly dependent on monomer concentration.…”
Section: Analysis Of Texture and Morphologysupporting
confidence: 82%
“…In conclusion, they stated that the type of the used solvent as well as the monomer to the solvent ratio are the most important factors, since they affect the pore structure [14]. On the other hand, according Sherrington et al the pore size distributions of almost all TRIM-based resins cover a broad range from micro-through meso-to macropores [2]. Notwithstanding, the BJH pore size distributions calculated from the desorption branch of the isotherm always exhibit a sharp, often large maximum in the PSD curve.…”
Section: Analysis Of Texture and Morphologymentioning
confidence: 98%
“…The effect of porogen on the morphology of beads has been well studied in the literature for free radical copolymerization of vinyl monomers. 33,56,57 In the former section, it has already been shown that the nature of the porogen is also important for beads derived from thiol-ene formulations ( Figure 4). The output is of interest where xylene is used as the sole porogen or mixed with nbutyl acetate ( Figure 7) instead of using pure n-butyl acetate for the thiol-yne formulations given in Figure 5.…”
Section: Porous Beadsmentioning
confidence: 90%
“…The Cu(II)-containing polymer beads were collected after washing in an acetone:water (1:1) solution four times and dried in vacuo for 1 day. The Cu(II)-imprinted polymer beads were obtained after removal of the copper ions in solution using aqueous 1.0 M HNO 3 with vigorous agitation [22]. The non-imprinted polymer was also prepared for comparison in chemical structure, except without use of the Cu 2+ solution.…”
Section: Synthesis Of Copper-imprinted Polymer Beadsmentioning
confidence: 99%